Optimization of the Runner Numerical Design Dimensions using the Simulation Program - Majernik, Jan; Gaspar, Stefan; Podaril, Martin; Kolinsky, Jan (Manufacturing Technology Journal, 2019)
The proper design of the gating system including the tempering and venting of the mold significantly influences the final quality of the casting and economize the costs of the foundries. The initial numerical design of the gating system is often sufficient for creating of the documentation for the mold design, but without the practical experience of the designer, it does not reveal the hidden problem emerging from the melt flow through the gating system as well as the temperature and gas mode of the mold.The contribution is dedicated to the optimization of the runner dimensions determined by the numerical calculation. The theoretical part presents the methodology, based on which the gating system was designed for a particular type of the pressure casting. The experimental part is dedicated to the influence of the cross sectional area of the runner on the change of the melt temperature before entering the ingate. It was assumed that the larger runner cross section gives the melt greater volume and heat capacity and thus the melt enters the ingate with the higher temperature. The obtained temperature results are then compared witht he melt flow rate values, based on which an optimal sulotion for the runner design dimensions is determined.
Keywords: High Pressure Die Casting; Runner; Construction; Technological Parameters